2010
DOI: 10.1109/tmech.2009.2030796
|View full text |Cite
|
Sign up to set email alerts
|

A Control Strategy for Upper Limb Robotic Rehabilitation With a Dual Robot System

Abstract: This paper describes the development and use of the cooperative control scheme used by the intelligent pneumatic arm movement (iPAM) system to deliver safe, therapeutic treatment of the upper limb during voluntary reaching exercises. A set of clinical and engineering requirements for the control scheme are identified and detailed, which entail controlled, coordinated movement of a dual robot system with respect to the human upper limb. This is achieved by using a 6-DOF model of the upper limb that forms the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
69
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(70 citation statements)
references
References 28 publications
0
69
0
1
Order By: Relevance
“…The human hand has many joints and performs important functions; therefore, injury to or loss of fingers is a serious problem. Prosthetic hands [7][8][9][10][11][12] and robotic devices that assist rehabilitation [13][14][15][16][17][18][19][20][21][22][23][24][25][26] are being developed in many institutes, and some prosthetic hands are available in the world market [7][8][9]. Robotic devices that assist rehabilitation are helpful in achieving an early recovery for injured patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human hand has many joints and performs important functions; therefore, injury to or loss of fingers is a serious problem. Prosthetic hands [7][8][9][10][11][12] and robotic devices that assist rehabilitation [13][14][15][16][17][18][19][20][21][22][23][24][25][26] are being developed in many institutes, and some prosthetic hands are available in the world market [7][8][9]. Robotic devices that assist rehabilitation are helpful in achieving an early recovery for injured patients.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic devices that assist rehabilitation are helpful in achieving an early recovery for injured patients. Devices that target the upper limb (shoulder or elbow, without hand) are currently being researched [13][14][15][16][17][18][19], while other work focuses on hand and finger function [20][21][22][23][24][25][26]. While research on prosthetic hardware has achieved a certain level, the next step must focus on how to control these devices.…”
Section: Introductionmentioning
confidence: 99%
“…These abnormalities are ascertained as disabilities and specific surgeries and rehabilitation exercises are implemented to recover body functions. The rehabilitation exercise has traditionally been performed by rehabilitation therapists, occupational therapists, and others for activating nerves and muscles in a disordered part through systematic and consistent repetitive exercises [3][4][5]9]. However, it is difficult to exactly estimate the degree of rehabilitation in patients due to the fact that the rehabilitation exercise is performed by simple repetitive actions and becomes passive exercises after a given period in addition to lacks of rehabilitation therapists.…”
Section: Introductionmentioning
confidence: 99%
“…The bilateral rehabilitation exercise has been used as a rehabilitation exercise method that improves the bilateral cooperation of both hands in stroke patients [4,12]. The efficacy of rehabilitation exercises has been verified through different studies in improving both the range of motion and the exercise performance in the affected part [3,4,11,12,19].…”
Section: Introductionmentioning
confidence: 99%
“…O'Malley, et al designed a PD trajectory controller with fixed gain to mange the Rice Wrist to serve the passive training [13]. Clumer, et al designed a 6-DOF iPAM rehabilitation system and adopted admittance controller to mange the passive training, the experimental results demonstrated that the admittance control method was able to serve the training stably and smoothly [14]. In general, the existing control methods for passive training are able to effectively stretch the impaired limb moving along the designed trajectory.…”
Section: Introductionmentioning
confidence: 99%